Preparation method of polymer dispersant applied to sodium electric main material slurry
Patent Information
- Application Number
- CN202611470094.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
Smart Images

Figure CN122992074A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to a method for preparing a polymer dispersant for use in sodium battery main material slurry. Background Technology
[0002] Currently, the main cathode material for sodium-ion batteries is a phosphate polyanionic system such as sodium iron pyrophosphate (NFPP), accounting for nearly 80% of the market share. In the preparation of sodium-ion battery cathode slurries, the main material is prone to gelation. Dispersants that perform well in lithium-ion batteries, such as polyether phosphates, polyacrylic acid, and small-molecule alkanolamines, have no significant dispersing effect in sodium-ion batteries and cannot improve the slurry's solids content. Currently, research on dispersants for sodium-ion battery cathode materials is limited.
[0003] For example, patent number CN118684812A, entitled "A Dispersant, Its Preparation Method and Sodium-ion Battery Positive Electrode Slurry Containing the Dispersant", describes a sodium polyacrylate battery dispersant prepared by copolymerization of acrylate monomers, vinyl acetate monomers and tert-carbonate monomers. This dispersant is suitable for the alkaline environment of sodium battery main materials and can improve the viscosity stability of the slurry.
[0004] For example, patent number CN117638039A, entitled "Preparation Method of Sodium-ion Battery Positive Electrode Slurry and Electrode with Improved Gel Formation," proposes functional small-molecule additives to solve the problem of easy gelation in sodium-ion battery slurries. The anti-gelling agents include glycolic acid, acetic acid, anhydrous oxalic acid, anhydrous citric acid, maleic anhydride, acetic anhydride, and their sodium salts. Patent CN122202326B uses acrylonitrile-acrylate copolymer, amine-containing condensate polymer, and small-molecule carboxylic acid additives as sodium-ion battery dispersants, which can effectively improve solid content and compaction density.
[0005] However, in the preparation of sodium-ion battery cathode slurries, the dispersant's effect on dispersing the sodium-ion battery main material is insufficient. Increasing the solid content of the slurry is easily limited by the increase in viscosity, making it difficult to balance high solid content with suitable viscosity. Simultaneously, the slurry is prone to viscosity rebound during storage, leading to insufficient slurry stability. Furthermore, using a single dispersing component or an unreasonable compounding system makes it difficult to simultaneously achieve both the initial dispersion performance and viscosity stability during storage. Therefore, this application provides a method for preparing a polymeric dispersant for sodium-ion battery main material slurries to meet these requirements. Summary of the Invention
[0006] The purpose of this application is to provide a method for preparing a polymer dispersant for use in sodium electrolytic main material slurries, which can effectively solve the problems mentioned in the background art.
[0007] To achieve the above objectives, this application provides the following technical solution: a method for preparing a polymer dispersant for use in sodium electrolytic main material slurries, comprising the following steps: (1) To prepare copolymer A, polyethyleneimine and amide compounds with long alkyl, benzene ring or naphthalene ring side chains are used as raw materials. In the presence of formaldehyde, the amide compounds are grafted onto the molecular chain of polyethyleneimine through the Mannich reaction to obtain copolymer A containing imino and long alkyl, benzene ring or naphthalene ring side groups on the molecular chain. (2) The copolymer A is mixed with acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate copolymer C and polyether D to prepare the polymer dispersant.
[0008] The molecular structure of copolymer A is shown in formula (Ⅰ): ; In formula (Ⅰ), R1 is -H or a C1~C4 alkyl group, a is the number of methylene groups and takes the value of 0 or 1. When a is 0, -Z is directly connected to the carbonyl group. x is the molar ratio of the structural unit, y is the molar ratio of the structural unit, and the sum of x and y is 1. The value of x ranges from 0.62 to 0.8. The long alkyl, benzene ring or naphthalene ring side group is represented by the group Z, where Z is a C10~C18 alkyl group, a group containing a benzene ring or a group containing a naphthalene ring.
[0009] Wherein, the group containing the benzene ring is Z-1, and the group containing the naphthalene ring is Z-2, and the structures of Z-1 and Z-2 are shown in formula (II): ; In formula (II), R2 is -H, C1~C4 alkyl, -OCH3, -OH or -F, and R2 is located at any substitution position on the benzene ring. R3 is -H, -OCH3, -OH or -F, and R3 is located at any substitution position on the benzene ring on one side of the naphthalene ring. The connection position of Z-2 with the polymer is located at the α or β position on the other benzene ring without substituent R3 in the naphthalene ring.
[0010] The amide compound is amide compound F, and its molecular structure is shown in formula (Ⅲ): ; In formula (Ⅲ), R1 is -H or a C1~C4 alkyl group, a is the number of methylene groups and takes the value of 0 or 1, when a takes the value of 0, -Z is directly connected to the carbonyl group, and Z is a C10~C18 alkyl group, a group containing a benzene ring or a group containing a naphthalene ring.
[0011] Wherein, the polyethyleneimine is a linear polyethyleneimine with a weight-average molecular weight of 800-20000; The formaldehyde is an aqueous solution with an effective content of 37%.
[0012] The molar amount of the amide compound is 0.62 to 0.8 times the molar amount of imino groups contained in the polyethyleneimine, and the molar amount of formaldehyde is 1.05 to 1.1 times the molar amount of the amide compound.
[0013] Specifically, the Mannich reaction in step (1) includes: S1: Dissolve polyethyleneimine in the solvent N-methylpyrrolidone, stir to dissolve, and then add formaldehyde; S2: Add an N-methylpyrrolidone solution of the amide compound dropwise at room temperature for 1 hour; S3: After the addition is complete, stir the mixture at room temperature for 6 hours to obtain copolymer A.
[0014] In step (2), the mass ratio of copolymer A, acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate copolymer C and polyether D is 70~95:1~8:1~5:3~20.
[0015] In step (2), the mass ratio of copolymer A, acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate copolymer C and polyether D is 80:5:3:12. After mixing thoroughly, the temperature should be raised to no less than 65°C, and a vacuum should be drawn to remove residual moisture and formaldehyde. The polymer dispersant exists in solution form and is dissolved in N-methylpyrrolidone solvent.
[0016] The vinylpyrrolidone-acrylate copolymer C has a weight-average molecular weight of 5000~35000, and its molecular structure is shown in formula (Ⅳ): ; In formula (Ⅳ), R4 is a C8~C12 alkyl group, m is the mass ratio of the structural unit, n is the mass ratio of the structural unit, the sum of m and n is 1, and the value of m ranges from 0.7 to 0.9. The polyether D is an addition product of ethylenediamine, diethylenetriamine, triethylenetetramine, or polyethylenepolyamine with ethylene oxide / propylene oxide, and has a weight-average molecular weight of 500-3000.
[0017] In summary, the technical effects and advantages of this invention are as follows: This invention employs a polymer dispersant composed of copolymer A, acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate copolymer C, and polyether D. The imino groups in copolymer A can form stable adsorption on the surface of the sodium-ion battery substrate, while the long alkyl, benzene ring, or naphthalene ring structures can inhibit adhesion between sodium-ion battery substrate particles through steric hindrance. This improves the dispersion state of the sodium-ion battery substrate in the slurry, allowing the slurry to have a higher solids content while maintaining a similar viscosity. The solids content of the slurry can be increased by 10% to 25%, thus solving the problem of sodium-ion battery cathode slurry's difficulty in achieving both high solids content and suitable viscosity.
[0018] This invention combines copolymer A with acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate copolymer C, and polyether D. This allows the nitrile, carboxylic acid, amide, tertiary amine, ether, and alkyl chain structures contained in each component to synergistically interact with copolymer A. This improves the initial dispersion state of the slurry while suppressing viscosity increases during storage, thereby enhancing the slurry's storage stability. As demonstrated in the examples, the polymer dispersant of this invention can significantly reduce the viscosity change rate of the slurry during 48 hours of storage. In some embodiments, the 48-hour viscosity change rate can be controlled within 15%, thus solving the problem of viscosity rebound that easily occurs during the storage of sodium electrode slurry.
[0019] This invention involves blending copolymer A, acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate copolymer C, and polyether D in a specific ratio, allowing each component to play its corresponding role. Copolymer A provides basic dispersion, acrylonitrile-acrylate copolymer B helps improve the initial dispersion state of the slurry, and vinylpyrrolidone-acrylate copolymer C and polyether D help improve the viscosity stability of the slurry during storage. This achieves a balance between the initial dispersion performance and storage stability of the slurry, avoiding performance degradation caused by a single dispersing component or an unreasonable blending ratio. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 This is a flowchart of a method for preparing polymer dispersants used in sodium electrolytic polymer slurries. Detailed Implementation
[0022] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] refer to Figure 1 The invention illustrates a method for preparing a polymer dispersant for sodium electrolytic main material slurry. This dispersant can increase the solid content of the slurry by 10% to 25% at the same viscosity and maintain a viscosity rebound rate of less than 15% within 48 hours.
[0024] The polymer dispersant consists of the main component copolymer A, and three auxiliary components: acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate copolymer C, and polyether D.
[0025] The mass ratio of copolymer A, acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate copolymer C, and polyether D is 70~95:1~8:1~5:3~20.
[0026] The polymer dispersant exists in solution form and is dissolved in N-methylpyrrolidone (NMP) solvent.
[0027] Copolymer A is a compound having the molecular structure shown in formula (I): ; In formula (Ⅰ), R1 is -H (H is the symbol for hydrogen) or a C1~C4 alkyl group. In the structural formula, C (=O) is a carbonyl group and O is the symbol for oxygen. a is the number of methylene groups, which can be 0 or 1. When a is 0, it means that -Z is directly connected to the carbonyl group. x is the molar ratio of the structural units, y is the molar ratio of the structural units, and the sum of x and y is 1. The value of x ranges from 0.62 to 0.8. Z is a C10~C18 alkyl group, or a group containing a benzene ring as shown in formula (Ⅱ) Z-1 or a group containing a naphthalene ring Z-2. ; In formula (II), R2 is -H, C1~C4 alkyl, -OCH3, -OH, or -F. R2 can be at any substitution position on the benzene ring. R3 is -H, -OCH3, -OH, or -F. It can also be at any substitution position on the benzene ring on one side of the naphthalene ring. The connection position of Z-2 with the polymer can be at the α or β position on the other benzene ring without substituent R3 in the naphthalene ring.
[0028] It is worth noting that copolymer A is synthesized from polyethyleneimine E and amide compound F via the Mannich reaction, and its specific preparation method is as follows.
[0029] S1: Add polyethyleneimine E and solvent NMP to the reactor, stir to dissolve, and then add formaldehyde.
[0030] S2: At room temperature, add NMP solution of amide compound F dropwise over a period of 1 hour.
[0031] S3: After the addition is complete, stir the reaction at room temperature for 6 hours.
[0032] In step S1, polyethyleneimine E is a commercially available industrial product, specifically a polyethyleneimine with a linear structure and a weight-average molecular weight of 800–20,000. Formaldehyde is also a commercially available industrial product, in the form of an aqueous solution with an effective content of 37%.
[0033] In step S2, amide compound F is a compound having the molecular structure shown in formula (Ⅲ).
[0034] ; In formula (Ⅲ), R1 is -H or C1~C4 alkyl, a is the number of methylene groups, which can be 0 or 1. When a is 0, it means that -Z is directly connected to the carbonyl group. Z is C10~C18 alkyl, or has a group containing a benzene ring as shown in formula (Ⅱ) Z-1 or a group containing a naphthalene ring Z-2. ; In formula (II), R2 is -H, C1~C4 alkyl, -OCH3, -OH, or -F, and R2 can be at any substitution position on the benzene ring. R3 is -H, -OCH3, -OH, or -F, and can be at any substitution position on the benzene ring on one side of the naphthalene ring. The connection position of Z-2 with the polymer can be at the α or β position of the other benzene ring without substituent R3 in the naphthalene ring.
[0035] In the above steps, the molar amount of amide compound F is 0.62 to 0.8 times the molar amount of imino groups contained in polyethyleneimine E, the molar amount of formaldehyde is 1.05 to 1.1 times the molar amount of amide compound F, and the amount of solvent NMP is sufficient to fully dissolve the reactants.
[0036] The synthesis method and molecular structure of acrylonitrile-acrylate copolymer B are fully disclosed in patent CN122202326B.
[0037] Ethylenepyrrolidone-acrylate copolymer C is a commercially available industrial product with a weight-average molecular weight of 5,000 to 35,000, and its molecular structure is shown in formula (Ⅳ).
[0038] ; In formula (Ⅳ), R4 is a C8~C12 alkyl group, m is the mass ratio of the structural unit, n is the mass ratio of the structural unit, the sum of m and n is 1, and the value of m ranges from 0.7 to 0.9.
[0039] Polyether D is a commercially available industrial product, which is an addition product of ethylenediamine, diethylenetriamine, triethylenetetramine or polyethylenepolyamine with ethylene oxide / propylene oxide, and its weight-average molecular weight is 500~3000.
[0040] The compound preparation process of polymer dispersant is as follows: First, the obtained copolymer A is mixed with acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate copolymer C, and polyether D in a composition mass ratio of 70~95:1~8:1~5:3~20. After mixing evenly, the temperature is raised to above 65℃, and then vacuum is applied to remove residual moisture and formaldehyde, thus obtaining polymer dispersant.
[0041] The polymer dispersant of this invention is added during the preparation of sodium battery cathode slurry at a dosage of 0.05% to 0.5% of the weight of the cathode material, and the dosage is the folded solids dosage. Too low a dosage will degrade its performance, while too high a dosage will result in economic waste without improving performance.
[0042] The polymer dispersant of the present invention has the following mechanism of action: (1) The molecular chain of copolymer A is rich in imino, long alkyl or benzene ring, naphthalene ring structure. Imino can form stable adsorption on the surface of sodium battery main material, while long alkyl or benzene ring, naphthalene ring structure has a suitable molecular volume and can prevent the main material from sticking through steric hindrance, thus giving copolymer A a good dispersion effect.
[0043] (2) The nitrile, carboxylic acid, amide, tertiary amine, ether, alkyl chain and other structures contained in acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate copolymer C and polyether D can have a synergistic effect with copolymer A, further enhancing the dispersion effect of copolymer A.
[0044] It is worth noting that the preparation process of copolymer A is described in detail. The synthesis principle of copolymer A can be found in the literature C. McDonald, R. Beaver, Macromolecules, 1979, 12(2), 203-208. All raw materials in copolymer A, linear polyethyleneimine, were purchased from Nippon Shokubai Co., Ltd. and all have linear structures. Amide F was purchased from Titan Technology Exploration Platform and formaldehyde was purchased from Sinopharm Chemical Reagent Company.
[0045] Synthesis Example A-1 S1: Add 160g of linear polyethyleneimine E-1 (weight average molecular weight 800, calculated to contain 3.72mol of imino groups) and 220g of solvent NMP to the reactor. After stirring and dissolving, add 265.9g of 37% formaldehyde aqueous solution (containing 3.28mol of formaldehyde).
[0046] S2: At room temperature, a solution consisting of amide compound F-1 benzamide (2.98 mol, 360.6 g) and NMP 1050 g was added dropwise over a period of 1 h.
[0047] S3: After the addition is complete, stir the reaction at room temperature for 6 hours.
[0048] After the reaction was completed, a sample was taken for GPC analysis, and the weight-average molecular weight of the product was found to be 2700. In synthesis example A-1, the molar ratio of imino groups in F-1 / E-1 was 0.8, and the molar ratio of formaldehyde to F-1 was 1.05.
[0049] Following the method of A-1, A-2, A-3, and A-4 were synthesized. The specific types and proportions of raw materials used are shown in Table 1.
[0050] Table 1; A-1 E-1, molecular weight 800 F-1, Benzamide 0.8 1.05 2700 A-2 E-2, molecular weight 5200 F-2, Octadecylamide 0.7 1.1 22000 A-3 E-3, molecular weight 10000 F-3, o-fluorobenzamide 0.65 1.1 28000 A-4 E-4, molecular weight 16000 F-4, α-Naphthylacetamide 0.75 1.1 55000 As shown in Table 1, the weight-average molecular weights of the linear polyethyleneimines E-1 to E-4 used in the synthesis examples A-1 to A-4 are 800, 5200, 10000, and 16000, respectively, covering the range of 800 to 20000 defined in this invention; the molar ratios of imino groups in amide compounds F and E are 0.8, 0.7, 0.65, and 0.75, respectively, and the molar ratios of formaldehyde to F are 1.05 or 1.1, all within the ranges of 0.62 to 0.8 and 1.05 to 1.1 defined in this invention.
[0051] Regarding the selection of amide compound F, F-1 benzamide and F-3 o-fluorobenzamide correspond to the group Z-1 containing a benzene ring in formula (II), where the benzene ring of benzamide is unsubstituted, i.e., R2 is -H, and the benzene ring of o-fluorobenzamide is substituted with fluorine at the ortho position, i.e., R2 is -F; F-4 α-naphthylacetamide corresponds to the group Z-2 containing a naphthalene ring, where the naphthalene ring is connected to a carbonyl group via a methylene group, i.e., α is 1; F-2 octadecylamide corresponds to the long-chain alkyl group Z of C10~C18 in formula (I).
[0052] The substituent R2 on the benzene ring can also be a C1~C4 alkyl, -OCH3 or -OH, and the substituent R3 on the naphthalene ring can also be -OCH3 or -OH. The naphthalene ring can be attached to the polymer at the α-position or β-position. The amide compounds with the above substituents can all be synthesized by referring to steps S1~S3 of Synthesis Example A-1 and undergoing the same Mannich reaction to obtain the corresponding copolymer A. Example 1
[0053] Example 1 verified the dispersion effect of the polymer dispersant of the present invention on sodium battery main material.
[0054] In the examples, acrylonitrile-acrylate copolymer B was prepared according to the method of synthesis example A-7 in patent CN122202326B, and the weight-average molecular weight was determined to be 205,000 by GPC.
[0055] The vinylpyrrolidone-acrylate copolymer C is from Jiangsu Yite New Materials Co., Ltd., and its synthesis process is as follows: 500 parts of solvent NMP are added to the reactor, the temperature is raised to 75°C, 3 parts of initiator benzoyl peroxide are added, and then a mixed solution consisting of 400 parts of vinylpyrrolidone and 100 parts of lauryl acrylate is added dropwise over 3 hours. After the addition is completed, the reaction is maintained at the temperature for 2 hours. Then the temperature is raised to 100°C, 1 g of initiator benzoyl peroxide is added, and the reaction is carried out for 1 hour to allow the residual monomers to fully polymerize.
[0056] The weight-average molecular weight of the product determined by GPC was 12,000. In the above copolymer C, the mass ratio of vinylpyrrolidone to lauryl acrylate was 400:100, and the mass ratio m of the corresponding structural unit was 0.8, which is within the range of 0.7 to 0.9 defined in this invention. The alkyl group of lauryl acrylate is lauryl, i.e., C12 alkyl, corresponding to R4 in formula (Ⅳ) being in the range of C8 to C12 alkyl; the weight average molecular weight of the product is 12,400, which is also within the range of 5,000 to 35,000 as defined in this invention.
[0057] Polyether D, sourced from Jiangsu Subote New Material Co., Ltd., is an addition product of 1 equivalent of diethylenetriamine with 18 equivalents of ethylene oxide and 21 equivalents of propylene oxide. GPC analysis showed a weight-average molecular weight of 1960 and a molecular weight distribution coefficient of 1.11, while HPLC analysis indicated an effective content of 98.4%. The weight-average molecular weight of 1960 for polyether D falls within the range of 500-3000 defined in this invention. The polyamine initiator for polyether D can also be ethylenediamine, triethylenetetramine, or polyethylenepolyamine, which can be added to ethylene oxide / propylene oxide respectively to obtain the corresponding polyether D.
[0058] The dispersant used in Example 1 is composed of copolymer A, acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate C and polyether D. When compounding, the raw materials are first mixed in a compositional mass ratio of 70~95:1~8:1~5:3~20, and more specifically 80:5:3:12. After mixing evenly, the mixture is heated to above 65°C, and then vacuumed to remove residual moisture and formaldehyde.
[0059] Within the above-mentioned mass ratio range, copolymer A is the main component, while copolymer B, copolymer C and polyether D act synergistically as auxiliary components. Those skilled in the art can adjust the specific ratio within the defined range according to the target viscosity and solid content of the slurry. Subsequent Example 4 shows that when the auxiliary components are missing or their ratio exceeds the above range, the dispersion and stabilization performance of the dispersant decreases.
[0060] Example 1 prepared four polymer dispersants, M being the sample number of the dispersant, numbered M-1, M-2, M-3, and M-4 respectively. The acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate C, and polyether D used in them were all the same, except that copolymers A-1, A-2, A-3, and A-4 were used respectively.
[0061] Table 2 verifies the dispersion of the polymer dispersant of the present invention on the sodium electrode substrate NFPP. The slurry was prepared from NFPP substrate:PVDF:SP:CNT:dispersant in a ratio of 95.2:2.5:1.5:0.5:0.3, wherein the dispersant content relative to the cathode substrate NFPP was approximately 0.32% (within the 0.05-0.5% content range specified in this invention). NMP solvent was then added to achieve a solid content of 55-68%. After homogenization using a vacuum degassing machine for 4 hours, the slurry viscosity was tested (cp is the viscosity unit centipoise). Simultaneously, the slurry was allowed to stand at 25°C for 48 hours, and its stability was monitored.
[0062] Table 2; blank 55 8574 13586 29188 240.4 M-1 67 8816 8745 9806 11.2 M-2 67 6884 6458 7634 10.9 M-3 67 7235 7066 7413 2.5 M-4 67 10785 9675 12502 15.9 As shown in Table 2, it can be seen that compared with the blank, the dispersants M-1 to M-4 prepared in this invention can increase the solid content of the slurry by 12 percentage points (from 55% to 67%) while maintaining a similar initial viscosity, proving that the polymer dispersants of this invention have good dispersing ability.
[0063] At 48 hours, the viscosity of the blank sample increased by 240.4%, while that of M-1 to M-4 remained below 16%, indicating that the polymer dispersants of this invention also have good viscosity stabilizing ability. M-2 exhibits the best initial dispersion ability, and M-3 exhibits the best viscosity stabilizing ability, while M-3 also has relatively good initial dispersion ability.
[0064] Table 3 shows the modified slurry ratio to further verify the dispersion of the polymer dispersant of the present invention on the sodium electrode main material NFPP. The slurry was prepared with a ratio of NFPP main material:PVDF:SP:CNT:dispersant = 95.6:2.0:0.35:1.8:0.25, where the dispersant content relative to the positive electrode main material NFPP was approximately 0.26% (solids equivalent). Also within the 0.05~0.5% content range specified in this invention, NMP solvent was added to achieve a solids content of 52~66%. The slurry was then homogenized using a vacuum degassing machine for 4 hours, and the viscosity was tested. Simultaneously, the slurry was allowed to stand at 25℃ for 48 hours, and its stability was monitored.
[0065] Table 3; blank 52 11359 35784 92876 717.6 M-1 66 11791 12075 12875 9.2 M-2 66 10857 11246 12633 16.4 M-3 66 11333 11574 12004 5.9 M-4 66 12060 13067 13593 12.7 As shown in Table 3, the conclusions remain unchanged, all demonstrating that the polymer dispersants of the present invention possess excellent dispersing ability. M-2 exhibits the best initial dispersing ability, while M-3 exhibits the best tack stabilizing ability, and M-3 also has relatively good initial dispersing ability. Example 2
[0066] Example 2 synthesized a copolymer A-5 using the same process as A-4 in Example 1, except that instead of linear polyethyleneimine E-4 (molecular weight 16000), linear polyethyleneimine E-5 (molecular weight 26000) was used. E-5 exceeds the limits set by this invention for the raw material polyethyleneimine. Subsequently, using the same ratio of 80:5:3:12, acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate copolymer C, and polyether D were added to obtain dispersant sample M-5. A slurry was prepared and its viscosity tested according to the method of Example 1.
[0067] Table 4; M-4 67 7235 7066 7413 2.5 M-5 67 25896 30185 45910 77.3 As shown in Table 4, the dispersing ability of M-5 is much weaker than that of M-4, which indicates that the molecular weight of the raw material polyethyleneimine exceeds the range defined in this invention, and its performance as a dispersant will be worse. Example 3
[0068] Example 3 synthesized a copolymer A-6 using the same process as A-3 in Example 1, but instead of o-fluorobenzamide, it was replaced with an equimolar amount of butyramide, which does not meet the limitations of the present invention for amide compound F. Subsequently, using the same ratio of 80:5:3:12, acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate C, and polyether D were added to obtain dispersant sample M-6. The viscosity of the slurry was tested according to the method of Example 1.
[0069] Table 5; blank 55 8574 13586 29188 240.4 M-3 67 10785 9675 12502 15.9 M-6 60 12654 16179 32067 153.4 As shown in Table 5, the dispersing ability of M-6 is far weaker than that of M-3. To achieve a similar initial viscosity, the solid content of M-6 needs to be 7 points lower, and the viscosity stabilization effect of M-6 is also relatively poor. This indicates that when using butyramide as a raw material, the butyl structure molecules it contains are small in size, with insufficient steric hindrance and weak molecular repulsion, thus failing to provide the excellent dispersing ability of M-3. However, compared with the blank, M-6 can improve the solid content by about 5 points, indicating that M-6 still has a certain dispersing ability.
[0070] In summary, amide compound F needs to have a certain degree of steric hindrance. For example, the scope of amide compound F defined in this invention is that F contains sterically hindered groups such as alkyl groups, benzene rings, and naphthalene rings of C10 to C18 in order to provide good dispersibility. Example 4
[0071] Example 4 prepared four dispersants according to Table 6 and the preparation method of Example 1, but with adjustments to the proportions of copolymer A, acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate copolymer C, and polyether D. Comparative Example 1 consisted only of copolymers A-3.
[0072] Comparative Example 2 contains all types of raw materials, but the proportions do not conform to the scope of this invention.
[0073] Comparative Example 3 is identical to M-3 except that it does not contain acrylonitrile-acrylate copolymer B. Comparative Example 4 is identical to M-3 except that it does not contain vinylpyrrolidone-acrylate copolymer C and polyether D, while the remaining copolymers A-3 and acrylonitrile-acrylate copolymer B are in the same proportion.
[0074] Table 6;
[0075] Table 7 shows the viscosity of the slurry prepared according to the method in Example 1 for testing M-3 and the comparative example.
[0076] Table 7; M-3 66 4113 3586 4447 8.1 Comparative Example 1 66 5514 6072 7001 27.0 Comparative Example 2 66 4405 4715 5134 16.5 Comparative Example 3 66 8765 8517 9054 3.3 Comparative Example 4 66 3993 4899 7345 83.9 As shown in Tables 6 and 7, compared with M-3, Comparative Examples 1 and 2 showed weaker initial dispersion and adhesion, indicating that the compound raw materials B, C, and D can improve performance. At the same time, the compound ratio of B, C, and D must be within the range defined by this invention, otherwise the performance will be affected.
[0077] Comparative Example 3, without B, showed insufficient initial dispersion but better tack performance. Comparative Example 4, without B but containing C / D, demonstrated that B is effective in improving initial dispersion and C / D is effective in improving tack. Example 5
[0078] Example 5 prepared two dispersants widely used in the lithium battery industry as shown in Table 8. They were mainly composed of polyether phosphate, polyvinylpyrrolidone, and alkanolamine, and were used to compare their performance with M-3.
[0079] Table 8;
[0080] Table 9 shows the viscosity of the slurry prepared according to the method in Example 1 for testing M-3 and the comparative example.
[0081] Table 9; blank 54 5089 9147 29086 471.5 M-3 66 4718 4569 5332 13.0 Comparative Example 5 55 4924 8276 12879 161.6 Comparative Example 6 56 5018 5891 7112 41.7 As shown in Table 9, compared to the blank, M-3 can improve solids by 12 percentage points, with a viscosity change rate of only 13% after 48 hours. Comparative Example 5 can only improve solids by 1 percentage point, with a viscosity rebound of 161.6% after 48 hours. Comparative Example 6 can improve solids by 2 percentage points, with a viscosity rebound of 41.7% after 48 hours. In summary, the polymer dispersant of this invention significantly enhances the dispersion performance of sodium battery main materials compared to traditional lithium battery polymer dispersants. Example 6
[0082] Example 6 verifies the effect of the polymer dispersant of the present invention on electrode compaction density and battery energy density.
[0083] The slurry was prepared according to the method in Example 5. The ground slurry was evenly and smoothly coated onto the aluminum foil current collector. After drying, it was cut into round pieces with a diameter of 1.2 cm.
[0084] A coin cell was assembled using a positive electrode disc, a separator, a sodium metal negative electrode, and sodium-ion battery electrolyte. The discharge specific capacity was then tested at different rates (0.1C and 1C). g is the unit of mass (gram), cm3 is the unit of volume (cubic centimeter), mAh is the unit of charge (milliampere-hour), the unit of compaction density is g / cm3, and the unit of discharge specific capacity is mAh / g. The results are shown in Table 10.
[0085] Table 10; M-3 2.42 148.3 139.7 Comparative Example 5 2.29 137.0 129.5 Comparative Example 6 2.31 138.9 131.1 As shown in Table 10, compared with Comparative Examples 5 and 6, M-3 has significant advantages in three tests: compaction density, discharge specific capacity at 0.1C rate, and discharge specific capacity at 1C rate, which can improve the battery energy density by approximately 7%.
[0086] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a polymer dispersant for use in sodium electrolytic polymer slurries, characterized in that, Includes the following steps: (1) To prepare copolymer A, polyethyleneimine and amide compounds with long alkyl, benzene ring or naphthalene ring side chains are used as raw materials. In the presence of formaldehyde, the amide compounds are grafted onto the molecular chain of polyethyleneimine through the Mannich reaction to obtain copolymer A containing imino and long alkyl, benzene ring or naphthalene ring side groups on the molecular chain. (2) The copolymer A is mixed with acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate copolymer C and polyether D to prepare the polymer dispersant.
2. The method for preparing a polymer dispersant for sodium-ion battery slurry according to claim 1, characterized in that: The molecular structure of copolymer A is shown in formula (Ⅰ): ; In formula (Ⅰ), R1 is -H or C1~C4 alkyl, a is the number of methylene groups and takes 0 or 1. When a takes 0, -Z is directly connected to the carbonyl group, x is the molar ratio of structural units, and y is the molar ratio of structural units. The sum of x and y is 1, and the long alkyl, benzene ring or naphthalene ring side group is represented by the group Z, wherein Z is a C10~C18 alkyl, benzene ring-containing group or naphthalene ring-containing group.
3. The method for preparing a polymer dispersant for sodium-ion battery slurry according to claim 2, characterized in that: The group containing the benzene ring is Z-1, and the group containing the naphthalene ring is Z-2. The structures of Z-1 and Z-2 are shown in formula (II): ; In formula (II), R2 is -H, C1~C4 alkyl, -OCH3, -OH or -F, and R2 is located at any substitution position on the benzene ring. R3 is -H, -OCH3, -OH or -F, and R3 is located at any substitution position on the benzene ring on one side of the naphthalene ring. The connection position of Z-2 with the polymer is located at the α or β position on the other benzene ring without substituent R3 in the naphthalene ring.
4. The method for preparing a polymer dispersant for use in sodium electrolytic main material slurry according to claim 1, characterized in that: The amide compound is amide compound F, and its molecular structure is shown in formula (Ⅲ): ; In formula (Ⅲ), R1 is -H or a C1~C4 alkyl group, a is the number of methylene groups and takes the value of 0 or 1, when a takes the value of 0, -Z is directly connected to the carbonyl group, and Z is a C10~C18 alkyl group, a group containing a benzene ring or a group containing a naphthalene ring.
5. The method for preparing a polymer dispersant for use in sodium electrolytic main material slurry according to claim 1, characterized in that: The polyethyleneimine is a linear polyethyleneimine with a weight-average molecular weight of 800-20000.
6. The method for preparing a polymer dispersant for use in sodium electrolytic main material slurry according to claim 1, characterized in that: The molar amount of the amide compound is 0.62 to 0.8 times the molar amount of imino groups contained in the polyethyleneimine, and the molar amount of formaldehyde is 1.05 to 1.1 times the molar amount of the amide compound.
7. The method for preparing a polymer dispersant for use in sodium electrolytic main material slurry according to claim 1, characterized in that: The Mannich reaction in step (1) specifically includes: S1: Dissolve polyethyleneimine in the solvent N-methylpyrrolidone, stir to dissolve, and then add formaldehyde; S2: Add an N-methylpyrrolidone solution of the amide compound dropwise at room temperature for 1 hour; S3: After the addition is complete, stir the mixture at room temperature for 6 hours to obtain copolymer A.
8. The method for preparing a polymer dispersant for use in sodium electrolytic main material slurry according to claim 1, characterized in that: The mass ratio of copolymer A, acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate copolymer C and polyether D in step (2) is 70~95:1~8:1~5:3~20.
9. The method for preparing a polymer dispersant for use in sodium electrolytic main material slurry according to claim 8, characterized in that: The mass ratio of copolymer A, acrylonitrile-acrylate copolymer B, vinylpyrrolidone-acrylate copolymer C and polyether D in step (2) is 80:5:3:12; After mixing thoroughly, the temperature should be raised to no less than 65°C, and a vacuum should be drawn to remove residual moisture and formaldehyde. The polymer dispersant exists in solution form and is dissolved in N-methylpyrrolidone solvent.
10. The method for preparing a polymer dispersant for use in sodium electrolytic main material slurry according to claim 1, characterized in that: The weight-average molecular weight of the vinylpyrrolidone-acrylate copolymer C is 5000~35000, and its molecular structure is shown in formula (Ⅳ): ; In formula (Ⅳ), R4 is a C8~C12 alkyl group, m is the mass ratio of the structural unit, n is the mass ratio of the structural unit, the sum of m and n is 1, and the value of m ranges from 0.7 to 0.
9. The polyether D is an addition product of ethylenediamine, diethylenetriamine, triethylenetetramine, or polyethylenepolyamine with ethylene oxide / propylene oxide, and has a weight-average molecular weight of 500-3000.
Citation Information
Patent Citations
Sodium-ion battery positive electrode slurry for improving gel, preparation method of pole piece and pole piece
CN117638039A
Dispersing agent, preparation method thereof and sodium ion battery positive electrode slurry containing dispersing agent
CN118684812A
Polymer dispersant for sodium-ion battery cathode material, sodium-ion battery
CN122202326B